2017
DOI: 10.1002/star.201700022
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic index of wheat bread

Abstract: Here, the concept and critical reviews concerning the glycaemic index are presented and the influence on human health with regard to the diets of various glycaemic indices are thoroughly reviewed. It is stated that wheat bread is regarded as high glycaemic index food, with some solutions having been proposed in order to reduce this indicator in three research areas: (i) the raw materials, (ii) the milling process, and (iii) bread-making along with the post-baking processes. Regarding the use of raw materials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 91 publications
(124 reference statements)
2
19
0
Order By: Relevance
“…There are several studies in which the influence of wheat and wholegrain bread consumption on the glycaemic response was studied. In these studies, just like in the present study, it was shown that after the consumption of wholegrain bread, the glycaemic response was lower in comparison to the glycaemic response after the consumption of bread prepared from purified flour (Figure 2) [38,39].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…There are several studies in which the influence of wheat and wholegrain bread consumption on the glycaemic response was studied. In these studies, just like in the present study, it was shown that after the consumption of wholegrain bread, the glycaemic response was lower in comparison to the glycaemic response after the consumption of bread prepared from purified flour (Figure 2) [38,39].…”
Section: Discussionsupporting
confidence: 73%
“…This product contained twice as much fibre as traditional waffles, and it might have increased the time needed to digest the carbohydrates present in the dough. The influence of dietary fibre and fat on the reduction of glucose levels in blood was also investigated by Borczak and Taye [39,42].…”
Section: Discussionmentioning
confidence: 99%
“…Eelderink et al [8] reported that a more compact bread structure, caused by different processing conditions, resulted in a healthier bread. In addition, a review conducted by Björzack et al [9] on the glycemic index of wheat bread stated that sourdough fermentation, reduced bread volume or kneading time, and long fermentations resulted in a reduction in glycemic index. From a digestive point of view, food structure can significantly affect the digestibility by modifying the degradation degree [5].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro digestion systems have been more than adequate for assessing the rate of carbohydrate digestion and absorption, namely the glycemic index [9]. These methods are useful for studying gastrointestinal food degradation without human intervention and provide an alternative to in vivo methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of postprandial glucose release can be described by its in vitro RAG and SAG values which are the main determinants of the glycaemic index of cereal-based foods [ 6 , 7 ]. Glycaemic index (GI) classifies carbohydrate foods based on how they influence postprandial plasma glucose response [ 8 ]. GI is expressed as the percentage increase in the glucose area under the curve of a test food against a standard food such as glucose or white bread [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%